The Convergence Between Non- Conviction Based Asset Forfeiture and Hudūd in Islamic Criminal Law - Orin Gusta Andini; Irma Suriyani; Hediansyah Hamzah; Radja Autar Sinaga (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2026)
Unlike other extraordinary crimes in Indonesia, such as terrorism and narcotics, which apply deradicalization and rehabilitation, corruption still lacks a recovery-oriented mechanism. One proposed solution is non-conviction-based asset forfeiture (NCB-AF) under the Asset Forfeiture Bill, although it remains controversial due to human rights concerns and debates over its purpose. In Islamic criminal law, hudūd punishment for theft, including hand amputation under strict conditions, aims to ensure justice and prevent reoffending. Using a normative legal method with statutory and conceptual approaches, this article finds that hudūd and NCB-AF share a similar goal: preventing repeat offenses and ensuring that crime does not remain profitable. Hand amputation symbolically cuts off the offender’s ability to reoffend, while NCB-AF cuts the economic lifeline the “blood of crime” that sustains criminal activity. The novelty of this study lies in linking these two concepts, while its contribution is offering a new perspective on the legitimacy and preventive function of NCB-AF in combating corruption.